2022
DOI: 10.1177/09722629221074771
|View full text |Cite
|
Sign up to set email alerts
|

Is Digital Business Model Innovation the Silver Bullet for SMEs Competitiveness in Digital Era? Evidence from a Developing Nation

Abstract: Digital business model innovation (DBMI) is often claimed to be a ‘game changer’ for SMEs in Malaysia. Small and medium-sized enterprises (SMEs) can use digital technology to coordinate business activities and create and deliver differentiated value to customers in both domestic and global markets. The literature on DBMI is sparse in the SME context. Therefore, semi-structured interviews were conducted with eight SME top managers to investigate how SMEs in manufacturing and service sector can implement DBMI (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
0
14
0
3
Order By: Relevance
“…According to Bourdon and Jaouen (2016), changing employees' resistance can be easily managed in large companies, but in SMEs, there is a magnification effect; the relative impact of an individual is multiplied (one employee out of ten means that 10% of workforce resists change). The employees may also not be committed to change due to additional workloads required, as reported by one of the case studies of Teoh et al (2022) of an SME that adopted digital BMI.…”
Section: Short Term Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Bourdon and Jaouen (2016), changing employees' resistance can be easily managed in large companies, but in SMEs, there is a magnification effect; the relative impact of an individual is multiplied (one employee out of ten means that 10% of workforce resists change). The employees may also not be committed to change due to additional workloads required, as reported by one of the case studies of Teoh et al (2022) of an SME that adopted digital BMI.…”
Section: Short Term Visionmentioning
confidence: 99%
“…The innovation strategy needs to encompass the conditions for using the technology and change the business (activities, value proposition, partnerships, the balance of revenue and cost) according to marketing opportunities. Top management should provide guidance, supervision, and training, especially in the first moment of technology introduction, to ensure that the employees can operate with new technology and do not commit repetitive mistakes (Teoh et al 2022).…”
Section: Enablers To Technological Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Temuan ini sejalan dengan penelitian yang dilakukan oleh Simamora et al (2020), Wardhana (2015), Fawaid (2017), Rahmana (2009). UMKM dapat menggunakan teknologi digital untuk mengkoordinasikan kegiatan bisnis dan menciptakan serta memberikan nilai yang berbeda kepada pelanggan baik di pasar domestik maupun global (Teoh et al, 2022). Dengan mengimplementasikan digital marketing khususnya, UMKM dapat memperluas wilayah pasar, meningkatkan komunikasi dengan konsumen, menempatkan konsumens sebagai partner yang memberikan input kepada UMKM yang berdampak pada daya saing UMKM.…”
Section: Hasil Pengujian Hipotesisunclassified
“…In addition, Teoh et al. (2022), Parida et al. (2019), and Verhoef & Bijmolt (2019) have suggested that future studies include an in‐depth investigate on DBMI, which strongly influences competitive advantage (Phillip, 2020), SME competitiveness (Mustafa et al., 2019; Taçoğlu et al., 2019), organizational performance (Bouwman et al., 2019; Verhoef & Bijmolt, 2019), and business sustainability (Wirtz, 2019; Del Giudice et al., 2022).…”
Section: Introductionmentioning
confidence: 99%